Optimalisasi Teknologi Digital Untuk Mencapai “UMKM Naik Kelas” Studi Kasus Toko Kelontong Kecamatan Genteng - Abd. Ghofar; Zawawi Zawawi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
For grocery stores in the Genteng area of Surabaya, digital technology, particularly in branding and digital marketing, can address the challenges faced by micro, small, and medium businesses in promoting and showcasing their products to potential customers. These stores have significant potential due to Genteng's strategic location and dense population. However, a major obstacle is the lack of understanding of digital advertising strategies and nuances, which hampers the growth of grocery stores and their ability to compete with modern retail companies. Observations and discussions with grocery store owners revealed this issue, prompting researchers to develop a research methodology and analysis of the existing challenges. Solutions offered include logo improvements, support with design and management of social media accounts and content, creation and management of marketplace accounts, and providing insights on Instagram advertising to business owners. With these various solutions, it is anticipated that grocery store entrepreneurs can compete effectively and keep pace with the rapid advancements in technology.